Relevansi Psikologi Komunikator Dalam Dunia Digital : Studi Kasus Postingan Akun Instagram Itsindahg LA VS Gaza - Muhammad Ridha; Asrizal Nazri; Irfan Nauval El Hassan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This research discusses the content analysis of Instagram social media with the account name itsindahg which contains videos related to the relationship between the fire in Los Angeles and the tragedy or colonization that occurred in Palestine which was uploaded in order to provide education to the digital community / netizens but apparently received attention from netizens which was conveyed via Instagram comments column on the post. This research uses library research, namely research that maximizes library materials originating from journals, books and other library materials to obtain information relevant to the research. The aim of this research is to determine the relevance of communicator psychology theory to Instagram content with the @indahG account with the title LA vs Gaza which contains educational videos related to the fire in Los Angeles and the tragedy or colonization that occurred in Palestine. The results of this research are that the psychological theory of communicators is relevant to Indah Gunawan's video content because Indah Gunawan is considered by netizens to be a content creator/influencer who does not have the credibility to discuss issues related to the occupation of Gaza even though it is linked to the disaster in Los Angeles.